Influence of Subject Matter Knowledge on Students’ Elective Mathematics Performance in Senior High Schools in Ghana: Does Teaching Experience Matter? - Ansah, Joseph Kweku; Mensah, Natalia; Wilmot, Eric Magnus (American Journal of Education and Learning, 2020)
This study examined the moderating role of teaching experience in the relationship between subject matter knowledge (SMK) and students’ performance in elective mathematics in Senior High Schools (SHS) in Ghana. The study employed the positivist philosophy in its enquiry. Specifically, the study was targeted at SHS in five regions (Central, Western, Northern, Greater Accra, and Ashanti). The population for this study comprised SHS 2 elective mathematics teachers and their corresponding elective mathematics students. Through a multi-stage sampling technique, 225 elective mathematics teachers were selected from 45 SHS in the five regions. For each of the teachers, 30 students were sampled from their classes to participate in the study. The mean performance of the students in each class was computed and associated with the respective teacher. The study revealed that SMK is a significant and positive predictor of students’ performance in elective mathematics. Despite the non-significant relationship revealed between teaching experience and students’ performance in elective mathematics, the results showed that teaching experience significantly moderated the relationship between SMK and the performance of students in elective mathematics. It is recommended to Ghana Education Service (GES) that, when hiring teachers with excellent subject matter knowledge, considerations should be given to those with much experience. Again, enough motivation should be provided for knowledgeable in-service elective mathematics teachers to remain in the classroom for longer periods, gaining the much-needed experience to improve the performance of elective mathematics in the senior high schools.